HMG-CoA reductase inhibitory activity of some selected Citrus hystrix constituents: in silico and in vitro evaluations - Singha, Suriphon; Thongchuang, Mayura; Siriwattanasathien, Yuttana; Sangiamdee, Duangkamon; Sutthivaiyakit, Somyote (Agriculture and Natural Resources, 2026)
Importance of the work: Compounds with high mobility group A (HMGA) moiety from Citrus hystrix could be an effective HMG-CoA (an intermediate in the mevalonate and ketogenesis pathways) reductase inhibitor as statin drugs. Objectives: To use in silico simulation and in vitro assay as tools to find HMG-CoA reductase inhibitor from Citrus hystrix constituents. Materials and Methods: A set of 23 compound structures from Citrus hystrix was identified and optimized using the Gaussian 09 software at the B3LYP/6-31G(d) level of theory and subsequently docked into the protein structures of HMG-CoA reductase (https://www.rcsb.org/structure/1HW9) to find the best hit. The molecular dynamic simulation and in vitro assay were investigated. Results: In total, 13 of the 23 compounds from C. hystrix had better molecular binding scores than simvastatin. Only three compounds—6ʹ-O-(3ʹʹ-hydroxy-3ʹʹ-methylglutaryl)- 6ʹ,7ʹ-dihydroxybergamottin (CH1), 6ʹ,7ʹ-dihydroxy-bergamottin and citrusoside G—that had high binding scores and were obtained in sufficient quantities—were chosen for further molecular dynamic simulation and in vitro HMG-CoA reductase inhibition assay. CH1 had better binding affinity than simvastatin, with both these having slightly different types and numbers of binding interactions. In the in vitro evaluation, CH1 had the strongest activity. However, the three compounds were less active than simvastatin. The discrepancy between the in vitro evaluation and in silico results may have been due partly to the limited solubility of the hydrophobic compounds in the test buffer solution used. Main finding: Evidence was provided that CH1 in C. hystrix was a promising HMG-CoA reductase inhibitor and this plant may be a useful functional food plant candidate for the treatment and alleviation of hyperglycemia and Alzheimer disease.